The NVivo qualitative project book - Bazeley, Patricia; Richards, Lyn (London ; Thousand Oaks, Calif. : SAGE Publications, 2000)
Accompanying CD-ROM contains demonstration software with data to help create a project about researchers and researching, and with multiple stages arranged sequentially in the development of a real project
Table Of Contents: Preface Introduction: The book and the software About this book About NVivo How can NVivo be used with this book? What other help is there? Making a start Where to start? Installing and calling NVivo Starting a project First steps Recording your initial thoughts Linking to other data Modeling your preliminary ideas Making it safe Taking stock First coding Nodes out of data Coding ``up'' from your project journal Workingt with retrievals More Free Nodes Viewing coding Exploring nodes Nodes in models Saving your project Taking Stock Making data Early data documents Edit or import? Importing a document Proxy documents Attributes and values Links to Memos (and other document) Creating and using memos Linking from the text to an existing document Linking a new memo Taking stock Working with data Reflecting and recording ideas Annotating the text Memoing detail Coding and what it does Thinking about coding Approaches to coding Coding in NVivo Coding at new nodes Coding at existing nodes Checking Coding Coding-on from a node Coding a proxy document Avoiding pitfalls in coding Reflections on a document Making a text report of your document Reflecting in a model Taking stock Shaping your project Creating more documents Nodes in Trees Coding with Tree Nodes Moving nodes Sets of documents Using Sets to direct a Search Sets of nodes Cases shaped in nodes Taking stock Emerging'' theory? What are you aiming for? How will you know if you get there? Theory emergence and theory construction Exploration of categories Working in a node Naming and describing A web of ideas Reflecting in a memo about a node Creating node links Extract Nodes Category development---focusing and extending Discriminating and combining categories Reviewing categories and seeking associations Modeling relationships Linking a model to a document Taking Stock Ordering concepts Thinking trees Sorting nodes From ``sorts'' to structure Creating Tree Nodes Shifting Free Nodes into Trees Rearranging an index tree Using structure Using trees while coding Using trees to explore with searches Taking stock Moving faster Batching in'' multiple documents Handling data from multiple sources Faster coding Coding with Text Search Combining text other searches Autocoding by section Faster attributes Faster Sets Faster cases Importing Attributes for Case Nodes Faster searches Using attributes to make comparisons Examining the interaction of attributes Taking Stock Getting there Aiming for and achieving research goals Categories and theory The project and its purposes Are your concepts good enough? Concept clarification Conceptual framework review Review the performance of nodes Concept clarification using searches Clustering concepts Exploring and validating patterns What is going on here? Seeking associations Under what conditions...? Investigating exceptions Fine reading, detailed understanding Insight, surprise and arrival Creating surprises Using (rather than losing) surprises When is an ``Aha'' a final chapter? Showing and Telling Making reports What next to learn about Nvivo? Appendix: Preparing Data Preparing a text document for import into NVivo Making notes or transcriptions Rich text documents Preparing open-ended survey responses Preparing a plain text document---with style Preparing data for attribute import Index
Includes index
System requirements: Windows 95,98, or Windows NT4; CD-ROM drive
Keywords: Social sciences -- Data processing; Qualitative research -- Data processing; Social sciences -- Methodology